Ethics and moral philosophy - Brooks, Thom (Studies in moral philosophy (Leiden, Netherlands), 2011)
Ethics and moral philosophy is an area of particular interest today. This book brings together some of the most important essays in this area. Topics include practical reason, particularism, moral realism, virtue ethics, and ethics and moral philosophy more generally.